Correction: Substrate and product binding inside a stimuli-responsive coordination cage acting as a singlet oxygen photosensitizer. Issue 32 (30th July 2020) - Pullen, Sonja; Löffler, Susanne; Platzek, André; Holstein, Julian J.; Clever, Guido H.
Abstract : Correction for 'Substrate and product binding inside a stimuli-responsive coordination cage acting as a singlet oxygen photosensitizer' by Sonja Pullen et al., Dalton Trans., 2020, 49, 9404–9410, DOI: ; 10.1039/D0DT01674H .